The profile of Lithuanian architects in relation to the professional generations active today - Riaubiene, Edita; Navickeinė, Eglė; Dijokienė, Dalia (Landscape Architecture and Art, 2023)
The research focuses on the professional profile of architects by analyzing their identity and creative principles. The aim is to explore the professional community of Lithuanian architects who are currently shaping the built environment, to identify their heterogeneity in terms of professional generations. The problem of the research is shaped by the current controversies in the field of architecture concerning the changing status, activities, and responsibilities of the architect. The relevance of the study lies in several aspects: the lack of in-depth sociological research on the professional community of Lithuanian architects; the attempt to verify and clarify the results of the semi-structured interview study Lithuanian Architects on Architecture, and the reflection on the global architectural situation and the new agenda for architectural design towards a high quality built environment. The study adopted a mixed methods research design. This involved the collection, analysis, and interpretation of both quantitative and qualitative data. This methodology is chosen because the research requires a complex and multifaceted approach to the phenomenon of architecture and the problems of architectural practice. It also allowed a larger group of research participants to be reached (450 respondents). The questionnaire contains 13 questions, each is structured in a multiple-choice format, with one option being an open-ended question. The questions are grouped under several themes: 1) the nature and fields of architectural practice and the concept of architecture; 2) the scope of practice and the allocation of professional time; 3) selfdetermination and professional loyalty; and 4) creative principles. Descriptive statistical methods were used to process the survey data. Content analysis and, to some extent, thematic analysis were used to analyze quantitative data from open-ended questions. The study highlights that the professional generations of architects analyzed follow the general trend of architecture, refuting the hypothesis that the approach of each generation is significantly different. However, it has been observed that the representatives of each generation show a particular attitude in a specific area, which indicates the dynamics of an attitude or predicts a change in the architectural community as a whole. The youngest generation of architects is an indicator of change. It is characterized by seeing a great diversity of aspects in architecture and architectural practice.